Pengaruh Online Promotion dan Location terhadap Keputusan Pembelian Hunian di Gemintang Residence Cileunyi - Rina Marlina Rahmawati; Riyan Hadithya (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The increasing competition in the property industry requires developers to optimize marketing strategies to enhance consumers' purchase decisions. Among various marketing factors, online promotion and location are considered essential determinants influencing housing purchase decisions. This study aims to examine the effects of online promotion and location on housing purchase decisions at Gemintang Residence Cileunyi. A quantitative approach with a causal associative design was employed. Data were collected through questionnaires distributed to 90 respondents selected using purposive sampling, consisting of prospective consumers who had visited Gemintang Residence and were familiar with its online promotional activities. The data were analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The findings indicate that both online promotion and location have positive and significant effects on housing purchase decisions, both individually and simultaneously. The Adjusted R² value of 0.531 indicates that the two variables explain 53.1% of the variance in purchase decisions, while the remaining 46.9% is influenced by other factors outside the proposed model. These findings highlight the importance of integrating digital marketing strategies with strategic location advantages to improve housing purchase decisions in the property sector.